2007
DOI: 10.4040/jkan.2007.37.7.1108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hand Acupuncture Therapy on Sleep Quality in Sleep Disrupted Adults: Verification by Polysomnography and Cerebral Blood Flow Test

Abstract: These results suggest that hand acupuncture therapy is effective for subjective sleep improvement only, not polysomnographical sleep indices and cerebral blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…수면 동안에 수축기 혈압과 심박동수를 5-15% 감소시켜 심장의 부담을 줄여준다 (Parish & Shepard, 1990). 수면증진을 위한 보완대체요법으로는 수지요법을 적용하여 성인의 수면의 질이 향상됨을 보고하였고 (Hwang, 2007), 이 완요법 (Park, 2007), 발반사 마사지 (Song, 2004) (Haddock, 1994;Topf, Bookman, & Arand, 1996). 병원 내에서 낮 동안의 소음 수준은 45 dBA, 밤 동안의 소음 수준은 35 dBA를 넘지 않도록 권장하고 있지만, 우리나라 중환자실의 수면시간대 소음정도는 이보다 훨씬 높은 것으로 보고되고 있다 (Jung, 2001;Son, 1999).…”
unclassified
“…수면 동안에 수축기 혈압과 심박동수를 5-15% 감소시켜 심장의 부담을 줄여준다 (Parish & Shepard, 1990). 수면증진을 위한 보완대체요법으로는 수지요법을 적용하여 성인의 수면의 질이 향상됨을 보고하였고 (Hwang, 2007), 이 완요법 (Park, 2007), 발반사 마사지 (Song, 2004) (Haddock, 1994;Topf, Bookman, & Arand, 1996). 병원 내에서 낮 동안의 소음 수준은 45 dBA, 밤 동안의 소음 수준은 35 dBA를 넘지 않도록 권장하고 있지만, 우리나라 중환자실의 수면시간대 소음정도는 이보다 훨씬 높은 것으로 보고되고 있다 (Jung, 2001;Son, 1999).…”
unclassified
“…Most of the acupuncture studies on insomnia have used only patient-reported outcomes; furthermore, even a small number of studies using objective outcomes such as polysomnography or actigraphy failed to show consistent results on the effect of acupuncture for each outcome. 30–34 Based on the results of this study, we expect that we will be able to compare the difference between the subjective and objective outcomes and contribute to solving the conflict on this issue. Only actigraphy is used for objective outcome measures at this time; however, polysomnography, a gold standard method for insomnia diagnosis, should be included in future research.…”
Section: Discussionmentioning
confidence: 96%
“… 28 29 However, there remain conflicting results regarding whether acupuncture has the same effect on both subjective and objective aspects of sleep. Some researchers argued that the effect of acupuncture was approved via both objective and subjective measurement tools, 25–27 while others reported that acupuncture seemed to affect the subjective outcomes only, not the result of polysomnography 30 31 or actigraphy. 32–34 …”
Section: Introductionmentioning
confidence: 99%